d13Ccarbonate chemostratigraphy of the Carrapateira Outlier (Lower Kimmeridgian), Southern Portugal - Borges, Marisa (2014)
The Carrapateira Outlier (CO) located 20 km north of Sagres is formed by Upper Triassic to Kimmeridgian sediments. The studied section is located at Três Angras bay and consists of approximately 50 m of limestones interbedded with marls, assigned to the Early Kimmeridgian based on corals, foraminifera and dinoflagellate cysts. The uppermost limestone beds are rich in macrofossils with well-preserved corals in life position. To compile 13C chemostratigraphy for this section, sixty five bulk carbonate samples were studied.